1998
DOI: 10.1046/j.1469-8137.1998.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiology of salt excretion in the xero‐halophyte Reaumuria hirtella

Abstract: Different aspects of salt excretion from leaves of the xero-halophyte Reaumuria hirtella Jaub. et Sp. (Tamaricaceae) were investigated under the extremely arid conditions of the desert. The diurnal excretion pattern, which gradually decreased toward midday, showed a negative correlation with the daily transpiration pattern. The relative excretion, which is the ratio between the absolute excretion of Na + and the change in its internal content, was maximal at sites with low salinity, and decreased when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 34 publications
1
36
0
5
Order By: Relevance
“…The classification of Chinese halophytes into three physiological types is based on salt uptake and storage, as described by Breckle (1995 Wang and Li 1993, and b from Chen et al 1990Chen et al , 1997; Desert Institute of Lanzhou in China Academy of Science 1986; Li and Wang 1990;Li and Zheng 1997;Li et al 2001;Lin 1990Lin , 1993Lin and Fu 1995;Ninxia Agriculture Prospesting College 1990;Ramadan 1998;Shao et al 2004;The Biology, Soils and Desert Institute of Xinjiang 1981;Wu 1980;Wu and Wang 1983;Xi et al 2006;Xiong and Li 1990;Zhao and Li 1999 mum, Halostachys, Suaeda, Glycyrrhiza, and Zygophyyllum. Hydrohalophytes are divided into emergent halophytes and submerged halophytes.…”
Section: Physiological Typesmentioning
confidence: 99%
“…The classification of Chinese halophytes into three physiological types is based on salt uptake and storage, as described by Breckle (1995 Wang and Li 1993, and b from Chen et al 1990Chen et al , 1997; Desert Institute of Lanzhou in China Academy of Science 1986; Li and Wang 1990;Li and Zheng 1997;Li et al 2001;Lin 1990Lin , 1993Lin and Fu 1995;Ninxia Agriculture Prospesting College 1990;Ramadan 1998;Shao et al 2004;The Biology, Soils and Desert Institute of Xinjiang 1981;Wu 1980;Wu and Wang 1983;Xi et al 2006;Xiong and Li 1990;Zhao and Li 1999 mum, Halostachys, Suaeda, Glycyrrhiza, and Zygophyyllum. Hydrohalophytes are divided into emergent halophytes and submerged halophytes.…”
Section: Physiological Typesmentioning
confidence: 99%
“…These structures, one of the forms of trichome found on the surface of the leaves of grasses, are termed 'microhairs' or 'salt glands' (Amarasinghe 1990; Amarasinghe andWatson 1988, 1989;Marcum and Murdoch 1992;Ramadan 1998). These microhairs are (with one exception amongst the grasses, see Flowers et al 1990) bicellular.…”
Section: Introductionmentioning
confidence: 97%
“…Salt glands also secrete considerable amounts of fluid in Limonium latifolum; under certain conditions the leaf discs secrete fluid up to half their weight in a 24-h period [38]. It has been reported that in Sporobolus spicatus the molar ratio of K þ /Na þ in the plant leaves was more than 10-fold that in the interstitial soil solution and 13 times that in the secreted salts, indicating the high selectivity of the secretion mechanism for sodium [39]. In addition to salt gland secretion, salts are also released through the cuticle or by guttation fluid, and they can be retransported back to the roots and soil via the phloem, or become concentrated in the salt hairs [40].…”
Section: Salt Secretion By Salt Glandsmentioning
confidence: 99%